Evaluation of AURKA rs2273535 and CDKN1B rs34330 Polymorphisms Association with the Risk of Breast Cancer - Atefeh Liravi; seyed Massoud Houshmand; Mojtaba Jafarnia; Mohsen Forouzanfar (Fasa University of Medical Sciences, 2022)
Background & Objective: Breast cancer consists of a heterogeneous group of tumours with different prognosis and is the most common cause of cancer-related mortality among women. In this study, our goal was to evaluate the association of AURKA rs2273535 and CDKN1B rs34330 polymorphisms with risk of female breast cancer in southwest part of Iran. Materials & Methods: This case-control study was done on 50 women with breast cancer and 50 healthy women without any symptoms or family history of breast cancer as the case and control group, respectively. Restriction fragment length polymorphism (RFLP- PCR) technique was designed to determine the AURKA rs2273535 and CDKN1B rs34330 gene polymorphisms. Afterwards, statistical analysis was done by means of SPSS (version 17). Results: In current research, our finding showed that rs2273535 T allele increased the susceptibility of breast cancer (OR:2.58, 95%CI:1.5-31.09, P=0.006). Moreover, T allele in dominant phase could raise the risk of the breast cancer (OR:3.01, 65%CI:1.31-6.92, P=0.009). However, the other polymorphism, CDKN1B rs34330, revealed no associations with increased risk of breast cancer. Conclusion: These findings suggest that AURKA rs2273535 may influence individual's susceptibility to breast cancer. But we found no associations regarding CDKN1B rs34330 polymorphism and this type of cancer.